Body Stereotypes on Google Images: How are Olympic and Paralympic Combat Sports Represented? - Tamarit Grancha, Ignacio; García Sottile, María Eugenia; Martín Ruiz, Julio; Gallego Cerveró, Clara; Ros Ros, Concepción; Ruiz-Sanchis, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
The study analyzes gender and body stereotypes in Olympic combat sports by looking at 500 Google images. Using a gender and intersectionality approach, a descriptive analysis was performed with Chi-square tests and Spearman's Rho correlation (p<.05). The results show a majority of representations of men (60.7%), predominantly Caucasian, adult and mesomorphic, while women are represented as young, ectomorphic with aesthetic elements. This reinforces traditional stereotypes of masculinity in these sports. In conclusion, gender inequalities persist in the visual representation of combat sports, consolidating traditional stereotypes.